Reception of Erich Hackl’s works in German speaking countries and in Poland - ŁAWNIKOWSKA-KOPER, Joanna (Transfer. Reception Studies, 2016)
Summary The paper researches the reception of the works of Erich Hackl in the German language speaking countries and in Poland in the contrastive aspect. The author presents the author and his works along with the genre (documentarism) and problem (influence of the totalitarian regimes on an individual) issues , then it refers to various circulations of reception in Po-land and German speaking countries. In German speaking countries, Hackl’s works are pre-sent in academic and critical circulation and, first of all, in the popular one, which is con-firmed by numerous entries at literary blogs, discussions at forums and Internet pages de-voted to the writer. There are only two short stories by the writer that are well-known in Po-land - these are, Farewell to Sydonia and Wedding in Auschwitz, that is why the reception of the writer’s works is limited mainly to these works.. At the same time, all his works are being discussed in the Polish academic circulation. What connects the reception of Hackl’s works in Poland and the German language speaking countries is the inclusion of his works into the educational programmes for the sake of tolerance and historical truth.